Islamic Thought and Human Rights View on Rights of Child: A Case of Child Domestic Workers In Indonesia - Firdaus Wajdi (Jurnal Studi Al-Qur'an, 2013)
Child Domestic worker is a problematic phenomenon in Indonesia. This phenomenon is not only related to poverty that is big problem in Indonesia. This phenomenon is related to education and many other factors. The child domestic workers are vulnerable to e exploited and face discrimination. So we need more effort to solve these problems. Actually the Islamic thought, Human Rights and Indonesian Constitutions are clear regulations to show what are the rights of children. The regulation also did not support the discrimination among child domestic workers, however we still see the child domestic workers related problems.